Effets De l’Acide Naphtalène Acétique, Du Type De Substrat Et De La Grosseur Des Boutures Sur Le Bouturage De Tige De Pterocarpus Erinaceus Poir. (Fabaceae) - Raoul, Bodjrenou Toundé; Towanou, Houètchégnon; Timothée, Keita N’Gna; Christine, Ouinsavi (European Scientific Journal, ESJ, 2018)
This study, conducted in south-east Benin, aims to provide practical information on the optimal conditions for successful propagation of stem cuttings of Pterocarpus erinaceus Poir. (Fabaceae), a real alternative to its regeneration and domestication. A trial was conducted to evaluate the effect of different doses of Acid Naphthalene Acetate (ANA) (0; 500; 750; 1000 and 1500 mg/l), the type of substrate (black forest sand and fine sand) and the size of the cuttings used ([1.5-2] and [2.5-3] cm of diameter) on the recovery of these cuttings. To evaluate the effect of different treatments on budding rate, bud burst rate and degenerate cuttings rate, Generalized Linear Mixed Models and Generalized Linear Models of the binomial family with the lme4 and nlme packages were used with the R.3.2.4 statistical software. The results showed that the application of ANA does not significantly improve the cuttings recovery. The probability of budding and budding with 0 mg / l of ANA is similar to that of 500 mg/l, and 750 mg/l of ANA ; doses of 1000 and 1500 mg/l of ANA significantly reduce the probability of budding and bud burst. The diameter of the stems of Pterocarpus erinaceus does not affect the recovery of the cuttings while the substrate has a marginal effect. Levels of degenerate cuttings during the trial do not vary with the treatments.